USING MOVING AVERAGES AND CANDLESTICKS TO INCREASE THE PROFIT POTENTIAL FOR INVESTORS - Indra, Yetti Afrida; Isnaini, Desi; Anggraini, Septi; Nurvadillah, Legi; Pardi, Abizar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The purpose of this study is to determine whether technical analysis using moving averages and candlesticks can simultaneously affect an investor's potential profit. The population in this study were FEBI students who had opened an account in 2021. With a sample of 71 students. The research method uses quantitative methods with an associative quantitative approach. The research instrument used was the distribution of questionnaires. The research data analysis technique is multiple linear regression to test the research hypothesis using the t-test and f-test using the SPSS 16 for windows software application. The results showed that the technical analysis variable (X1), moving average (X2) and candlestick (X3) had a simultaneous influence on potential investment returns. It can therefore be said that the content of the hypothesis is accepted.